Perancangan Solar Fish Cooler untuk Meningkatkan Kualitas dan Keberlanjutan Ikan Segar di Pantai Jenu Tuban - Susanto, Aldi; Kalista, Anggia; Wibowo, Moh. Muhyidin Agus; Anggraini, Susanti Dhini (Universitas Kadiri, 2023)
Jenu Tuban Beach has natural beauty and an abundance of fish which is the source of livelihood for local residents. However, fish catches often experience freshness during trips to the market due to the use of fish coolers that are not optimal. In order to avoid financial losses for fishermen, the development of fish coolers with better technology and automatic cooling rate is indispensable. Currently, the fish cooler used is still ineffective and prone to damage, so it is necessary to develop better technology. This process involves identifying the needs of fishermen through direct interviews and questionnaire design, as well as testing validity and consistency. The results of identification and technical response are designed in the House of Quality matrix, and are processed by determining both relationships by prioritizing Raw Weight results. Solar Fish Cooler can maintain fish temperature for 3 hours with cooling level up to -200C. This tool operates with sunlight energy and is suitable for use in areas that are difficult to reach conventional electricity sources. The main priorities in improving product quality are the duration of long-lasting cooling, the level of temperature stability and ease of product repair. The development was carried out by combining temperature and humidity sensor technology. Research on these tools can contribute to the development of technologies and the reduction of fossil fuel use in the field of sustainable fisheries.